Automatic synthesis of VHDL Hardware Components from IOPT Petri Net models - Pereira, Fernando (2014)
Conferência: 39th Annual Conference of the IEEE Industrial-Electronics-Society (IECON), Vienna, Austria, Nov 10-14, 2013